2010
DOI: 10.1007/s11240-010-9740-6
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development

Abstract: We developed a new protocol for highly efficient somatic embryogenesis and plantlet conversion of Schisandra chinensis. Friable embryogenic callus was induced from cotyledonary leaves and hypocotyls of germinated zygotic embryos on Murashige and Skoog (MS) agar medium containing 2,4-dichlorophenoxyacetic acid (2,4-D). Preculture of zygotic embryos on 2,4-D-containing medium increased embryogenic callus induction efficiency. The highest embryogenic callus induction frequency of 56.7% was obtained from shoot api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…Another important finding, in this study is, the massive production of somatic embryos from yellow friable callus cultured on EG medium supplemented with 100 lM calcium ionophore A23187. Somatic embryogenesis has been achieved under the influence of BA or KN in combination with IAA in many plants viz, C. arabica (Menendez-Yuffa et al 2010), Pulsatilla koreana Nakai , Ochna integerrima (Ma et al 2011), Desmodium motorium (Chitra Devi and Narmathabai 2011), Crambe abyssinica (Don Palmer and Keller 2011), Dendrocalamus hamiltoni , Schisandra chinensis (Chen et al 2010) and Colocasia esculenta (Deo et al 2010). In the present study, IAA and KN have been used during initial stage of embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another important finding, in this study is, the massive production of somatic embryos from yellow friable callus cultured on EG medium supplemented with 100 lM calcium ionophore A23187. Somatic embryogenesis has been achieved under the influence of BA or KN in combination with IAA in many plants viz, C. arabica (Menendez-Yuffa et al 2010), Pulsatilla koreana Nakai , Ochna integerrima (Ma et al 2011), Desmodium motorium (Chitra Devi and Narmathabai 2011), Crambe abyssinica (Don Palmer and Keller 2011), Dendrocalamus hamiltoni , Schisandra chinensis (Chen et al 2010) and Colocasia esculenta (Deo et al 2010). In the present study, IAA and KN have been used during initial stage of embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous application of auxin has been demonstrated as an efficient treatment for the induction of somatic embryos, but further development of somatic embryos commonly occurs by reducing or removing auxin from the culture media (Jiménez 2005;Huang and Yeoman 1984;Mordhorst et al 1998;Chen et al 2010). For example, Halperin and Wetherell (1964) reported that the somatic embryos of carrot (Daucus carota) formed from the embryogenic callus after reducing the concentration of 2,4-D. Pillon et al (1996) induced early-stage Arabidopsis thaliana somatic embryogenesis by treatment with 4.5 lmol/L 2,4-D for 21 days and somatic embryos formed following their transfer to an auxin-free medium.…”
Section: Induction Of Somatic Embryosmentioning
confidence: 99%
“…This is probably because, prevalence of optimal concentration of inorganic nutrients in the culture medium results in a favorable optimal osmotic potential for dedifferentiation of embryogenic callus. The inhibitory effects of high MS strength on SE development have been reported in other plant species (Choi and Jeong 2002;Chen et al 2010). Sugar not only provides the required carbon sources for plant growth, but in its original form it also influences the osmotic potential in the culture medium.…”
Section: Role Of Osmoticummentioning
confidence: 84%